Situação econômica de arranjos domiciliares monoparentais e biparentais no Brasil: uma análise orçamentária - Marcia Barroso Fontes (2014)
This paper aims to explore the economic situation of single parent households compared to two-parent households, considering the possibility of both is reacquainted with and without extended family. Possession of consumer information, even if it covers investment made by parents to their children, the components capable of enhancing the human capital of the same. Through the National Research by Household Sample (PNAD) and the Household Budget Survey (POF), defines the types of living arrangements and it appears as subclassifications of these arrangements are associated with budgetary perspective, using the methods Ordinary Least Squares (OLS) and Seemingly Unrelated Regressions (SUR). Thus, identifying the profile of the different arrangements measured by income, expenditure and asset ownership, beyond the agenda of spending on components investment indicators in children, encourages the discussion of the necessity of planning policy which has as axis families, assuring them the greater well-being and quality of life of individuals.